Sensorless control of dual three-phase permanent magnet vernier machine for ship propulsion - Teymoori, Vahid (Stellenbosch : Stellenbosch University, 2025)
Teymoori, V. 2025. Sensorless Control of Dual Three-Phase Permanent Magnet Vernier Machine for Ship Propulsion. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/da2adfd7-10f9-488f-8342-7277554c9aea